The Effect of Authority, Empathy, Honesty on the Management of Education Personnel - Muhamad, Muhamad; Ali, Hapzi; Anwar, Kasful (International Journal of Advanced Multidisciplinary, 2023)
Educational staff is one of the important factors in the overall educational driving force. Management of educational staff aims to utilize educational staff effectively and efficiently to achieve optimal results. The purpose of this research is to reveal the actual activities of educational management and staffing and to find out the efforts made to improve the quality of education through education and staffing management. Education personnel can be said to be one of the keys to the success or failure of education, so it is necessary to understand what the nature of the management of education personnel is and the aspects of managing educational staff. Management can be interpreted as organizing or managing so that something that is managed can run smoothly, effectively and efficiently. Management can also be interpreted as carrying out activities by utilizing all existing resources, which have been planned to be implemented and evaluated regularly according to certain procedures in order to achieve predetermined goals. While aspects of the management of educational staff consist of planning, recruitment, training and fair development. The type of approach used in this research is qualitative with a qualitative descriptive research method. Research subjects, school principals, 1 administrative staff, 1 teacher. This research data collection technique is to use interviews, observation and documentation. This data analysis technique is carried out by means of the reduction stage, data presentation, and drawing conclusions.